Migration and Strategic Urban Planning - Bernt, Matthias (DISP, 2019)
This paper discusses the so-called “local turn” in the governance of migration and integration as expressed in the relevant literature. The study focuses on how and to what extent migration-related issues have been reflected in urban development strategies in the east German city of Leipzig over the past 20 years. Based on the analysis of planning documents and interviews with experts and decision-makers, the paper shows that urban planning strategies have increasingly recognized the role of and adapted to immigration. However, migration has certainly not yet become the central focus of planning strategies. Moreover, there is a mismatch between the immigration of sought-after “high potentials” and “creative types”, and actual migration which is dominated by refugees. Whereas the first group is targeted through marketing campaigns and specific place-based policies, the latter is by and large subject to welfare state policies. The paper discusses three major factors that serve to explain this double orientation and argues that they create massive barriers to making migration a more central issue in urban planning. In sum, the paper takes a somewhat sceptical view of the “local turn” and cautions against using studies with few cases on limited policy fields to generalise about urban governance trends.